AKTIVITAS ANTHELMINTIKA EKSTRAK ETANOL DAN EKSTRAK KLOROFORM RIMPANG BENGLE (Zingiber purpureum Roxb.) TERHADAP CACING Ascaridia galli Schrank SECARA IN VITRO BESERTA PROFIL KROMATOGRAFI LAPIS TIPIS - Intan Permata Dewi; Wiharni Wiharni; C.J. Soegihardjo; Endang Darmawan (Universitas Islam Indonesia, 2005)
ABSTRACTPurple ginger (Zingiber Purpureum Roxb.) could be use as therapy for ascariasis. Theanthelmintic activity test by in vitro has been tested to get the validity of the effect. The maincomponents of the test is powder of purple ginger rhizoma which had been extracted bypercolation method with ethanol and maseration method with kloroform. Anthelmintic test had beendone by immersion method. The Ascaridia galli Schrank was soak in natrium chloride 0,9 %,pyrantel 0,125 %, extract ethanol 0,702 %, 1,404 %, 2,808 %, 5,616 % and exstract kloroform0,644 %, 1,288 %, 2,576 %, 5,152 %. From the test it could be concluded that the extract has theanthelmintic effect. The result evolution had been done by one way ANOVA method (P